Recent Progress of Porous Materials in Lithium‐Metal Batteries. Issue 5 (27th January 2021) - Liu, Yao; Zhai, Yunpu; Xia, Yongyao; Li, Wei; Zhao, Dongyuan
Abstract : Lithium‐metal batteries (LMBs) are regarded as one of the best choices for next‐generation energy storage devices. However, the low Coulombic efficiency, lithium dendrite growth, and volume expansion of lithium‐metal anodes are dragging LMBs out of successful commercialization. Herein, the application of various porous materials in LMBs is focused on. First, several representative works are summarized to highlight the recent key progress of porous materials in LMBs, categorized into current collectors, thin 3D "hosts, " protection layers, and separators. Then, the existing challenges are discussed and future research needs to present more thorough characterizations of porous materials are advocated for, such as their porosity, electric conductivity, specific surface area, and mass density, to elaborate on their positive influence on electrochemical performance. Finally, future strategies with porous materials to build long‐cycle‐life, high‐energy‐density lithium‐metal full cells toward realistic performance targets are envisioned. Abstract : Recent progress of porous materials as current collectors, thin 3D "hosts, " protection layers, and separators for lithium‐metal anodes is summarized. The existing challenges and future research directions are discussed to facilitate the practical development of lithium‐metal batteries.